Pengaruh Pengetahuan Perbankan Syariah dan Religiusitas terhadap Minat Mahasiswa Perbankan Syariah untuk Memilih Bekerja di Perbankan Syariah: Studi Pada Mahasiswa Perbankan Syariah UINSU Angkatan 2018 - Nurfuadi, Wika; K, Kamilah; Harahap, Muhammad Ikhsan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine the effect of religiosity and Islamic banking knowledge on the interest of Islamic banking students class of 2018 to choose to work in Islamic banking at UIN-SU faculties of economics and business. The data collection method in this study was the questionnaire method, namely distributing a list of statements (questionnaires) that would be filled out or answered by respondents to Islamic banking students class of 2018. To manage and analyze the data obtained and make research conclusions, quantitative analysis was used with multiple linear regression analysis techniques. which aims to obtain a comprehensive picture of the relationship between variables with the help of the SPSS (Statistical Package For Social Sciences) Version 2.9 program. The test results show that knowledge of Islamic banking has a significant effect on the interest of Islamic banking students to choose to work in Islamic banking, and religiosity has a significant effect on the interest of Islamic banking students to choose to work in Islamic banking. The predictive ability of these two variables on the interest of students to have careers in Islamic financial institutions is 46.7% while the rest is influenced by other external factors. Keywords: Knowledge of Islamic Banking, Religiosity and Interest in Working in Islamic Banking